STRATEGIES AND CHALLENGES IN EMPOWERING A PRE-SERVICE ENGLISH TEACHER WITH PHYSICAL DISABILITIES: AN AUTOETHNOGRAPHY - Saiful, Jepri Ali (LLT Journal: A Journal on Language and Language Teaching, 2025)
Promoting inclusivity in language teacher education is essential for advancing pedagogical justice and fostering a socially equitable education system. However, research and practice in this area, particularly on mentoring teachers with disabilities, remain scarce. Most existing scholarship has focused on students with disabilities rather than pre-service teachers with disabilities. Addressing this gap, this autoethnographic study examines the researcher’s experiences mentoring a pre-service English teacher with limb-girdle muscular dystrophy, who relied on a wheelchair, was unable to walk or write, yet aspired to pursue a career as an English teacher. Over one and a half years of mentorship, the researcher documented strategies and challenges through personal reflections and analysis of journals and interviews with stakeholders. Three strategies proved essential: adopting an inclusive mindset through differentiated instruction, actively listening to the student and his family, particularly in online learning and thesis supervision, and selecting a special school as the site for his teaching practicum. Three major challenges also emerged: addressing epistemic injustices and professional acceptance, coping with the absence of shadow lecturers and accessible infrastructure such as libraries and digital smartboards, and navigating restricted employment opportunities. These findings underscore the urgency of equitable accommodations for aspiring English teachers with physical disabilities.